2017
DOI: 10.1079/pavsnnr201712025
|View full text |Cite
|
Sign up to set email alerts
|

Review of microbial zoonoses in slaughterhouses and identified potential critical risk points along red meat processing chain in Nigeria.

Abstract: Slaughterhouses are key locations where contamination occurs along the processing chain of red meat. Bearing in mind that there are high levels of zoonotic and food-borne diseases in Nigeria, a search was conducted, with the exploration and filtration of databases and repositories of Google Scholars, African Journal Online, PubMed and ResearchGate, for scientific publications in Nigeria between 2001 and 2016; slaughterhouse/abattoir, microbial, meat-borne diseases, zoonoses, Nigeria are the search words. Abatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is a preventative approach to food safety (FSA, 2005). Fasanmi et al (2017b), identified more CCPs (12) for abattoir when compared with the slaughter slab (9) with muddled up activities during slaughtering, thereby leading to difficulties in the monitoring, prevention and control of probable hazard(s). The numbers of CCPs positively correlate with level of hygiene and cleanliness; and hence there is lower tendency of contamination.…”
Section: Discussionmentioning
confidence: 99%
“…It is a preventative approach to food safety (FSA, 2005). Fasanmi et al (2017b), identified more CCPs (12) for abattoir when compared with the slaughter slab (9) with muddled up activities during slaughtering, thereby leading to difficulties in the monitoring, prevention and control of probable hazard(s). The numbers of CCPs positively correlate with level of hygiene and cleanliness; and hence there is lower tendency of contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, dried meat microbiology has involved a natural development of wild fermentation in which microbial successions occur; however, homogeneous salting over the entire surface is most important to suppress pathogens and spoilage organisms [ 8 ]. Meat and meat products, on the other hand, provide an ideal environment for pathogenic microorganisms including Listeria monocytogenes, Salmonella spp., Campylobacter spp., and verotoxigenic Escherichia coli to thrive, posing the largest risk of meat-borne diseases [ [ 6 , 9 ]]. Due to the presence of foodborne pathogens, dried foods, especially meat products, have been increasingly documented to be involved in outbreaks and recalls [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diseases caused by foodborne pathogens such as bacteria, viruses, and parasites may influence human health and the local/global economy significantly. Recently, pathogenic factors in slaughterhouses for foodborne diseases have been studied extensively [8,9]. Since contamination risk from foods, water, fomite, environment, and wastes is always possible for these pathogens, studies, especially in enterprises producing raw meat, on these pathogens have become very important for human health [10].…”
Section: Introductionmentioning
confidence: 99%